Biliary tract reconstruction using jejunal tube: an experimental study in dogs - Trentini, Eliane Amain; Crema, Eduardo; Llanos, Juan Carlos [UNESP]; Lerco, Mauro Masson [UNESP]; Magna, Luiz Alberto; Leonardi, Luiz Sergio (Zhejiang Univ Sch Medicine, 2009)
BACKGROUND: To physiologically reconstruct the biliary tract, Crema et al suggested the application of the Monti principle to the biliary tract, already used in humans for the urinary tract. With this technique, a jejunal segment is transversely retubularized. This study aimed to evaluate the efficacy of jejunal tube interposition between the common bile duct and duodenum in dogs.METHODS: Thirteen dogs underwent a laparoscopic common bile duct ligature, followed by a biliodigestive connection by jejunal tube interposition after one week. The levels of glutamic-pyruvic and glutamic-oxalacetic transaminases, total bilirubins, alkaline phosphatase and gamma-glutamyltransferase were assessed before surgery and thereafter weekly until euthanasia, which was performed 6 weeks after biliodigestive connection.RESULTS: Data on 9 dogs were analyzed statistically. The dogs presented with obstructive jaundice after common bile duct ligature, as confirmed by biochemical examination. They showed a statistically significant reduction in cholestasis after biliodigestive connection by jejunal tube interposition and were healthy until the end of the experiment.CONCLUSION: A statistically significant reduction was seen in total bilirubin and canalicular enzymes (alkaline phosphatase and gamma-glutamyltransferase) in the 9 dogs 6 weeks after biliodigestive conviction by jejunal tube interposition.
Keywords: biliary tract surgical procedures; monti principle; obstructive jaundice